Algunos malos detestables sucios completamente asquerosos pero-- invisibles germenes - Rice, Judith, 1953-; Merrill, Reed; Ytsma, Petronella J. (St. Paul, MN : Redleaf Press, 1997)
A little girl, who accumulates germs on her hands during her busy day, defeats them by washing her hands before meals.
English and Spanish.
Keywords: Children -- Health and hygiene -- Juvenile literature; Hand washing -- Juvenile literature; Bacteria -- Juvenile literature; Viruses -- Juvenile literature; Health -- Juvenile literature; Hygiene -- Juvenile literature; Spanish language materials -- Bilingual -- Juvenile literature